A Peptide Mimicking VGLL4 Function Acts as a YAP Antagonist Therapy against Gastric Cancer - Jiao, Shi; Wang, Huizhen; Shi, Zhubing; Dong, Aimei; Zhang, Wenjing; Song, Xiaomin; He, Feng; Wang, Yicui; Zhang, Zhenzhen; Wang, Wenjia; Wang, Xin; Guo, Tong; et al. (Cancer cell, 2014)
The Hippo pathway has been implicated in suppressing tissue overgrowth and tumor formation by restricting the oncogenic activity of YAP. However, transcriptional regulators that inhibit YAP activity have not been well studied. Here, we uncover clinical importance for VGLL4 in gastric cancer suppression and find that VGLL4 directly competes with YAP for binding TEADs. Importantly, VGLL4’s tandem Tondu domains are not only essential but also sufficient for its inhibitory activity toward YAP. A peptide mimicking this function of VGLL4 potently suppressed tumor growth in vitro and in vivo. These findings suggest that disruption of YAP-TEADs interaction by a VGLL4-mimicking peptide may be a promising therapeutic strategy against YAP-driven human cancers. [Display omitted] •VGLL4 is a potential tumor suppressor and prognostic marker in gastric cancer•VGLL4, via its tandem TDU domain, directly competes with YAP for binding to TEADs•A peptide functionally mimicking VGLL4 potently inhibits gastric cancer growth•Ratio of YAP to VGLL4 could serve as a prognostic marker for personalized therapy Jiao et al. show that VGLL4 competes with YAP for binding to TEAD coactivators and, in this manner, VGLL4 acts as a tumor suppressor in gastric cancer. The authors utilize this knowledge to devise a VGLL4 peptide mimic that inhibits YAP oncogenic activity and acts therapeutically against gastric cancer.